STORAGE CONDITION AND PERIOD EFFECT ON THE DIMENSIONAL STABILITY OF IRREVERSIBLE HYDROCOLLOID IMPRESSION MATERIALS - Nurhat Özkalaycı; Ayşegül Köroğlu; Çağla Börekçi (Cumhuriyet Dental Journal, 2017)
The aim of this study was to evaluate the effects of brand, holding solution and storage periods on dimensional stability of irreversible hydrocolloid impression materials.Impressions were taken from a master maxillary typodont, using a newly designed device and five different irreversible hydrocolloid impression materials. A total of 245 impressions were taken and divided into a control group, two main groups and three subgroups through storing procedure and time. Stone models were obtained for each model and five different dimensions were measured and compared to each other. Comparison of the groups according to brand of irreversible hydrocolloid impression materials showed statistically significant differences. While the storage period was statistically important at all distances, storage condition was significant only at some distances.